How do you simplify (6w ^ { 2} - w - 7) ( w ^ { 2} + 2w - 5)?

1 Answer
May 5, 2018

omega = 7/6 , -1, (sqrt6 - 1) and (-sqrt6 - 1)

Explanation:

Let omega be x

Assuming that this equation = 0

:. As per the question,

(6x^2 - x - 7)(x^2 + 2x - 5) =0

(6x^2 +6x - 7x - 7)(x + sqrt6 +1)(x - sqrt6 + 1) = 0

[6x(x + 1) -7(x + 1)][(x + sqrt6 +1)(x - sqrt6 + 1) = 0

[(6x-7)(x+1)][(x + sqrt6 +1)(x - sqrt6 + 1) = 0

:. x = 7/6 , -1, (sqrt6 - 1) and (-sqrt6 - 1)

But x = omega

:. omega = 7/6 , -1, (sqrt6 - 1) and (-sqrt6 - 1)